European Crises and Right-Wing Populism: The Case of Lega Nord - Balla, Evanthia (2022)
This study adopts a threefold narrative. Firstly, it offers a conceptual analysis of right-wing populism in a post-truth age. This section focuses on the definitions and links between European right-wing populism and the post-truth. The second section discusses the relationship between the crises, the rise of populism and the post-truth age. It shows that since the beginning of the twenty-first century, the European Monetary Union’s (EMU) weaknesses, as well as the financial and refugee crises were capitalised by right-wing populist parties. Populist right-wingers thus took advantage of this decline of trust to mobilise economic polarisation and nativist sentiments, spreading a particular anti-EU rhetoric. However, in a post-truth environment, right-wing populist parties have been able to spread their political rhetoric as never before, extensively using social media as a platform for direct, yet unrestrained, communication with the public. This has resulted in unprecedented electoral success at national and European levels – further challenging democratic values and the European project itself. The third part focuses on a case study of the Italian Lega Nord – which was not originally a right-wing populist party, instead belonging to a populist and ethno-regionalist party family rooted under a pro-EU and anti-statism ideology. However, in order to respond to the challenges of European integration, the party has progressively loosened its original features and joined the right-wing populist party family. Therefore, Lega Nord’s transformation helps shed light on the link between the accretion of right-wing populism and the European crises. Lega Nord’s Matteo Salvini has been the European leader that has used social media the most in his political campaigns over recent years, reaching more than 3,000,000 followers in 2018 (Cervi 2020). Such a successful strategy has allowed Lega to reach the best electoral results in its history in the national election of 2018 and in the European elections of 2019. In this vein, Lega shows how the post-truth age has allowed the spreading of rightwing populist ideology as never before, threatening European democratic values and the European Union political project.